Periodontal referral patterns in Norway: 2003 versus 2018 - Kristian H. Lind; Dagmar F. Bunæs; Stein Atle Lie; Knut N. Leknes (Wiley, 2022)
Abstract Objectives Changes in periodontal referral patterns over time have been reported from the United States and Australia. To date, comparable studies have not been published from Europe. The objectives of the present study were to examine changes in periodontal referral patterns in Norway in 2003 versus 2018 and to compare these with trends observed in the United States and Australia using universal criteria for grading of periodontal severity. Materials and methods A retrospective analysis of 369 charts from four Norwegian periodontics clinics was completed. Data on year of referral, gender, age, tobacco smoking, periodontal status and missing teeth at initial examination, teeth planned for extraction, and periodontal case type were collected using a survey format; case type I, II, III, and IV representing increasing severity of periodontitis, case type V representing referral for other periodontal conditions (peri‐implantitis, refractory periodontitis, etc.). Chi‐square, t‐tests, and negative binomial regression were used for the statistical analysis. Results Compared with 2003, the 2018 data showed an increase in mean age at referral (p < 0.05), overall distribution of case type III and V (p = 0.047), and number of missing teeth (p = 0.001). Further, a decrease in prevalence of smokers (p < 0.05), but no change in number of teeth planned for extraction (p = 0.104), were observed. Conclusions During a period of 15 years, changes in periodontal referral patterns in Norway are similar to those in the United States and Australia. The adoption of a guideline‐based referral practice might be beneficial for both the dental profession and patients.